PENGARUH PERILAKU BELAJAR, KETERAMPILAN SOSIAL, DAN KEANGGOTAAN DI UKM TERHADAP WAKTU PENYELESAIAN STUDI - Yuwanti Kurnia Sari; Kurniawan Ali Fachrudin (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2015)
The time of study completion is a matter that need to be taken into account by students during the learning process. In this case, students have considered an adults who could be responsible for themselves and their activities. They are given the freedoom to follow the various of Students Activity Unit (UKM) since entered Ahmad Dahlan University. In the process of election, the students are able to choose the activity accordance with their interests and talents. By following the Students Activity Unit, they are expected to have a good social skill. This study aims to determine the influence of learning behavior, social skills, and membership in Students Activity Unit (UKM) on the time of study completion. The population are bachelors degree students of Accounting Studies Program at Ahmad Dahlan University, with criteria sampling of students who had been followed the final examination. This study took sample of 40 respondents with using purposive sampling method. Based on the data results of the test which has been done by using multiple regression model, showed that whole of independent variable (behavior learning, social skills, and membership Students Activity Unit) has no effect toward the dependent variable (the time of study completion).